Process method for preparing composite phosphate

Through the composite phosphate preparation process, the problems of unstable degluing ability and uniformity of existing clay degluing agents are solved, and the efficient and uniform degluing effect is achieved, which improves the fluidity and gloss of clay, which is suitable for construction Ceramic products in the decoration industry.

CN119143091APending Publication Date: 2024-12-17GUIZHOU FUQUAN CHUANDONG CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302648.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The degreasing ability and uniformity of existing clay degreasing agents are unstable, which affects the fluidity and gloss of clay. The technical threshold is low, making it difficult to meet the demand for efficient and uniform degreasing in the construction and decoration industry.

Method used

The composite phosphate preparation process is adopted, and the pH value and phosphorus pentoxide content are controlled through the preparation and polymerization of the neutralizing liquid, and the purification is carried out by physical chromatography filtration and heating precipitation method to prepare a composite with stability and efficient degluing. Phosphate.

Benefits of technology

It achieves stable process and efficient glue decoction, improves the fluidity and gloss of clay, optimizes the appearance molding effect of ceramics, has stable product quality and high technical threshold. It is suitable for self-healing acrylate photosensitive resin for 3D printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143091A_ABST
    Figure CN119143091A_ABST
Patent Text Reader

Abstract

The invention discloses a composite phosphate and a process method. The composite phosphate is prepared through the procedures of neutralizing to prepare slurry, preparing the composite phosphate from the slurry, detecting and the like. The composite phosphate prepared by adopting the method disclosed by the invention is prepared by one-step molding, controllable in production process, stable in product quality and relatively high in technical threshold, has a good clay peptizing effect and an effect of increasing the flowing effect in a clay production process, and has positive effects on the molding glossiness and smoothness of a clay product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of clay disintegrator preparation, and in particular to a process for preparing composite phosphate. Background Art

[0002] The main function of clay dissolving agent is to help dissolve the glue stuck on the surface of clay, so as to achieve the effect of removing glue. Clay dissolving agent is widely used in cleaning glue on the surface of ceramics, glassware, mosaics, tiles, etc. High-quality clay dissolving agent is also suitable for enhancing the fluidity of clay and improving the glossiness of clay, especially affecting the appearance of finished tiles. Clay dissolving agent is widely used in the construction and decoration industry. One-time molding clay dissolving agent is a new type of dissolving agent with great development prospects.

[0003] Because the existing clay degumming agents are mostly a single type of phosphate or a mechanically mixed phosphate, the technical threshold is low, the degumming ability and uniformity are uneven and unstable, and some degumming agents have an adverse effect on the fluidity and glossiness of the clay.

[0004] Therefore, there is an urgent need on the market for a process for preparing composite phosphates that is stable, efficient in degumming, and fully uniform, can promote the fluidity of clay, and can optimize the appearance of ceramics. Summary of the invention

[0005] The present invention aims to provide a self-healing acrylic photosensitive resin for 3D printing, which has stable process, efficient degumming, and overall uniformity, promotes the fluidity of clay, and optimizes the appearance of ceramics, and a method for manufacturing the same.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a composite phosphate and a process method, comprising the following stages: S1: Raw materials and equipment preparation ① Raw material preparation: prepare sufficient raw materials such as soda ash, disodium iodide, phosphoric acid and auxiliary materials such as sodium nitrate, sodium sulfide and hydrogen peroxide; ② Equipment preparation: prepare neutralization pot, slurry pump, high-level storage tank, atomization device, polymerization device with integrated polymerization kettle and drying kettle, cooler, elevator, product silo; S2: Neutralization to prepare slurry ① Add 20%-40% water to the measured raw materials of soda ash, disodium ions, phosphoric acid and water obtained in step ① of stage S1, then add disodium ions with a phosphorus content of 20%-80% and phosphoric acid with a phosphorus content of 20%-80% into the neutralization pot, and then add soda ash with an alkali content of 20%-80%, heat with a steam coil and maintain at 100℃±15℃, stir and mix until the two disodium ions are completely dissolved, adjust the pH value to 8.1-8.5, and the specific gravity to 1.35m 3-1.55kg / m 3 Within the range of, adding 0.1%-0.2% sodium sulfide, 0.2%-0.3% sodium nitrate, and 0.05%-0.1% hydrogen peroxide containing the solid amount of the material to obtain a neutralizing solution; ② Transfer the neutralization solution obtained in step ① into the high-level tank using a slurry pump; S3: Slurry preparation of composite phosphate ① Preheating the polymerization furnace prepared in step ② of stage S1, wherein the preheating fuel is yellow phosphorus tail gas whose main component CO accounts for 65% to 70% of the total gas volume, and then heating the polymerization furnace for preheating, when the preheating temperature reaches 450°C, maintaining the heating, keeping the temperature at 445°C to 455°C, and then evenly feeding; ② The process parameters of the feeding process are as follows: the neutralizing liquid in the high-level tank is atomized at a pressure of 5MPa to 10MPa and a frequency of 30Hz to 40Hz, and is sent to the polymerization furnace at a gas flow rate of 65m3 / min to 80 / min. The neutralized slurry is sucked into the high-pressure pump by the negative pressure generated by the high-pressure pump, and then pressurized to 5MPa-10MPa, and then sent to the polymerization furnace for polymerization and drying. The polymerization parameters are 400℃ to 500℃, the polymerization time is 45min to 60min, and the liquid level gauge on the top of the high-level tank is used for measurement; at the same time, the neutralizing liquid in the high-level tank is continuously replenished to keep the liquid level of the high-level tank at 1 / 2 to 3 / 4 of the total volume. The high-pressure pump adjusts the delivery pressure through the regulating valve to keep the pressure within the range of 5MPa to 10MPa. ③ The neutralized slurry is sent to the polymerization furnace under the pressure of the high-pressure pump in the high-level tank; the polymerization reaction is carried out at a temperature of 430°C to 470°C, and the phosphate complex salt obtained by the polymerization is dried by the heat of the reaction system; then the material in the polymerization furnace is dried and transferred to the cooling device for cooling. After cooling to room temperature, the cooled material is sent to the elevator and transported to the product silo to obtain prefabricated composite phosphate; ④ The prefabricated composite phosphate obtained in step ③ is sampled and tested; its pH value is between 9.2 and 9.6, phosphorus pentoxide is between 52.5% and 55.5%, and iron is less than 300ppm. If the test is qualified, it is the composite phosphate to be tested; ⑤ The composite phosphate obtained in step ④ is subjected to a peptization test, and the peptization technical parameters are: clay flow rate <60m 3 / s, if it is qualified, it is the required composite phosphate.

[0007] In the above-mentioned process for preparing a composite phosphate, the prefabricated composite phosphate obtained in step ③ of stage S3 is supplemented with purification, specifically, the prefabricated composite phosphate is fully dissolved in a sufficient amount of deionized water, and the solution is purified using a physical chromatography filtration device, the filtration structure of the physical chromatography filtration device is a mixed solid filtration device composed of three types of activated carbon with a particle size of 1μm-2μm and alumina powder with a particle size of 0.1μm-0.2μm; the purified solution is salted out by a heating precipitation method, and the salted out solid is dried to obtain the desired purified prefabricated composite phosphate.

[0008] Compared with the prior art, the present invention has the following advantages due to the adoption of the above technical solution: (1) The composite phosphate prepared by the method of the present invention is prepared by one-step molding, the production process is controllable, and the product quality is stable.

[0009] (2) The technical threshold of the present invention is relatively high, especially the exploration of process parameters and various detailed parameters, which are gradually clarified, improved and finally determined in the long-term production process. They are the crystallization of production experience of continuously adjusting the production process in accordance with customer needs.

[0010] (3) The present invention controls the process, especially the key indicators "PH value between 9.2 and 9.6, phosphorus pentoxide between 52.5% and 55.5%, iron <300ppm, and the peptization technical parameters are: clay flow rate <60m 3 / s”, so that the present invention can increase the flow effect of the clay production process, and has a positive effect on the gloss and smoothness of the clay product molding.

[0011] (4) The preferred prefabricated composite phosphate supplementary purification process is to use the phosphate precipitation method to remove excess iron impurities in the extract in a one-step precipitation, and then remove other impurities by physical adsorption filtration to obtain a more purified composite phosphate with the least impurities.

[0012] Therefore, the present invention has the characteristics of stable process, efficient degumming, overall uniformity, promoting clay fluidity, and optimizing ceramic appearance molding. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Finite element simulation of the temperature in the reaction area of ​​the slurry prepared by the present invention; Figure 2 This is a picture of the physical product of the present invention; Figure 3 The quality inspection report of the present invention; Figure 4 This is a physical picture of the production equipment of the present invention. DETAILED DESCRIPTION Example

[0014] One method is to use Figure 4 The equipment shown is produced as Figure 2 , Figure 3 The process for preparing the composite phosphate shown comprises the following stages: S1: Raw materials and equipment preparation ① Raw material preparation: prepare sufficient raw materials such as soda ash, disodium iodide, phosphoric acid and auxiliary materials such as sodium nitrate, sodium sulfide and hydrogen peroxide; ② Equipment preparation: prepare neutralization pot, slurry pump, high-level storage tank, atomization device, polymerization device with integrated polymerization kettle and drying kettle, cooler, elevator, product silo; S2: Neutralization to prepare slurry ① Such as Figure 1 As shown in the simulation, the raw materials of soda ash, disodium ions, phosphoric acid and water obtained in step ① of stage S1 are measured, and 20%-40% of water is added first, and then disodium ions with a phosphorus content of 20%-80% and phosphoric acid with a phosphorus content of 20%-80% are added to the neutralization pot, and then soda ash with an alkali content of 20%-80% is added, and the mixture is heated with a steam coil and maintained at 100℃±15℃. The mixture is stirred and mixed until the two disodium ions are completely dissolved, and the pH value is adjusted to 8.1-8.5, and the specific gravity is 1.35m 3 -1.55kg / m 3 Within the range of, adding 0.1%-0.2% sodium sulfide, 0.2%-0.3% sodium nitrate, and 0.05%-0.1% hydrogen peroxide containing the solid amount of the material to obtain a neutralizing solution; ② Transfer the neutralization solution obtained in step ① into the high-level tank using a slurry pump; S3: Slurry preparation of composite phosphate ① Preheating the polymerization furnace prepared in step ② of stage S1, wherein the preheating fuel is yellow phosphorus tail gas whose main component CO accounts for 65% to 70% of the total gas volume, and then heating the polymerization furnace for preheating, when the preheating temperature reaches 450°C, maintaining the heating, keeping the temperature at 445°C to 455°C, and then evenly feeding; ② The process parameters of the feeding process are as follows: the neutralizing liquid in the high-level tank is atomized at a pressure of 5MPa to 10MPa and a frequency of 30Hz to 40Hz, and is sent to the polymerization furnace at a gas flow rate of 65m3 / min to 80 / min. The neutralized slurry is sucked into the high-pressure pump by the negative pressure generated by the high-pressure pump, and then pressurized to 5MPa-10MPa, and then sent to the polymerization furnace for polymerization and drying. The polymerization parameters are 400℃ to 500℃, the polymerization time is 45min to 60min, and the liquid level meter on the top of the high-level tank is used for measurement; at the same time, the neutralizing liquid in the high-level tank is continuously replenished to keep the liquid level of the high-level tank at 1 / 2 to 3 / 4 of the total volume, and the high-pressure pump adjusts the delivery pressure through the regulating valve to keep the pressure within the range of 5MPa to 10MPa; ③ The neutralized slurry is sent to the polymerization furnace under the pressure of the high-pressure pump in the high-level tank; the polymerization reaction is carried out at a temperature of 430°C to 470°C, and the phosphate complex salt obtained by the polymerization is dried by the heat of the reaction system; then the material in the polymerization furnace is dried and transferred to the cooling device for cooling. After cooling to room temperature, the cooled material is sent to the elevator and transported to the product silo to obtain prefabricated composite phosphate; ④ The prefabricated composite phosphate obtained in step ③ is sampled and tested; its pH value is between 9.2 and 9.6, phosphorus pentoxide is between 52.5% and 55.5%, and iron is less than 300ppm. If the test is qualified, it is the composite phosphate to be tested; ⑤ The composite phosphate obtained in step ④ is subjected to a peptization test, and the peptization technical parameters are: clay flow rate <60m 3 / s, if it is qualified, it is the required composite phosphate. Example

[0015] The main part is related to Example 1, except that: S3: Slurry preparation of composite phosphate ③ The neutralized slurry is subjected to the pressure of the high-pressure pump in the high-level tank and is sent to the polymerization furnace; the polymerization reaction is carried out at a temperature of 430°C to 470°C, and the phosphate complex obtained by the polymerization is dried by using the heat of the reaction system; the material in the polymerization furnace is then dried and transferred to a cooling device for cooling. After cooling to room temperature, the cooled material is sent to an elevator and transported to a product silo to obtain a prefabricated composite phosphate; the prefabricated composite phosphate is supplemented and purified, specifically, the prefabricated composite phosphate is fully dissolved in a sufficient amount of deionized water, and the solution is purified by a physical chromatography filtration device, the filtration structure of the physical chromatography filtration device is a mixed solid filtration device composed of three types of activated carbon with a particle size of 1μm-2μm and alumina powder with a particle size of 0.1μm-0.2μm; the purified solution is salted out by a heating precipitation method, and the salted solid is dried to obtain the desired purified prefabricated composite phosphate; The above description of the disclosed embodiments is intended only to enable those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A process for preparing a composite phosphate, characterized in that The following phases are included: S1: Raw materials and equipment preparation ① Raw material preparation: prepare sufficient raw materials such as soda ash, disodium iodide, phosphoric acid and auxiliary materials such as sodium nitrate, sodium sulfide and hydrogen peroxide; ② Equipment preparation: prepare neutralization pot, slurry pump, high-level storage tank, atomization device, polymerization device with integrated polymerization kettle and drying kettle, cooler, elevator, product silo; S2: Neutralization to prepare slurry ① Add 20%-40% water to the measured raw materials of soda ash, disodium ions, phosphoric acid and water obtained in step ① of stage S1, then add disodium ions with a phosphorus content of 20%-80% and phosphoric acid with a phosphorus content of 20%-80% into the neutralization pot, and then add soda ash with an alkali content of 20%-80%, heat with a steam coil and maintain at 100℃±15℃, stir and mix until the two disodium ions are completely dissolved, adjust the pH value to 8.1-8.5, and the specific gravity to 1.35m 3 -1.55kg / m 3 Within the range of, adding 0.1%-0.2% sodium sulfide, 0.2%-0.3% sodium nitrate, and 0.05%-0.1% hydrogen peroxide containing the solid amount of the material to obtain a neutralizing solution; ② Transfer the neutralization solution obtained in step ① into the high-level tank using a slurry pump; S3: Slurry preparation of composite phosphate ① Preheating the polymerization furnace prepared in step ② of stage S1, wherein the preheating fuel is yellow phosphorus tail gas whose main component CO accounts for 65% to 70% of the total gas volume, and then heating the polymerization furnace for preheating, when the preheating temperature reaches 450°C, maintaining the heating, keeping the temperature at 445°C to 455°C, and then evenly feeding; ② The process parameters of the feeding process are as follows: the neutralizing liquid in the high-level tank is atomized at a pressure of 5MPa to 10MPa and a frequency of 30Hz to 40Hz, and is sent to the polymerization furnace at a gas flow rate of 65m3 / min to 80 / min. The neutralized slurry is sucked into the high-pressure pump by the negative pressure generated by the high-pressure pump, and then pressurized to 5MPa-10MPa, and then sent to the polymerization furnace for polymerization and drying. The polymerization parameters are 400℃ to 500℃, the polymerization time is 45min to 60min, and the liquid level gauge on the top of the high-level tank is used for measurement; at the same time, the neutralizing liquid in the high-level tank is continuously replenished to keep the liquid level of the high-level tank at 1 / 2 to 3 / 4 of the total volume. The high-pressure pump adjusts the delivery pressure through the regulating valve to keep the pressure within the range of 5MPa to 10MPa. ③ The neutralized slurry is sent to the polymerization furnace under the pressure of the high-pressure pump in the high-level tank; the polymerization reaction is carried out at a temperature of 430°C to 470°C, and the phosphate complex salt obtained by the polymerization is dried by the heat of the reaction system; then the material in the polymerization furnace is dried and transferred to the cooling device for cooling. After cooling to room temperature, the cooled material is sent to the elevator and transported to the product silo to obtain prefabricated composite phosphate; ④ The prefabricated composite phosphate obtained in step ③ is sampled and tested; its pH value is between 9.2 and 9.6, phosphorus pentoxide is between 52.5% and 55.5%, and iron is less than 300ppm. If the test is qualified, it is the composite phosphate to be tested; ⑤ The composite phosphate obtained in step ④ is subjected to a peptization test, and the peptization technical parameters are: clay flow rate <60m 3 / s, if it is qualified, it is the required composite phosphate.

2. A process for preparing a composite phosphate according to claim 1, characterized in that: The prefabricated composite phosphate obtained in step ③ of stage S3 is subjected to additional purification, specifically, the prefabricated composite phosphate is fully dissolved in a sufficient amount of deionized water, and the solution is purified by a physical chromatography filtration device, wherein the filtration structure of the physical chromatography filtration device is a mixed solid filtration device composed of three types of activated carbon with a particle size of 1μm-2μm and aluminum oxide powder with a particle size of 0.1μm-0.2μm; the purified solution is salted out by a heating precipitation method, and the salted out solid is dried to obtain the desired purified prefabricated composite phosphate.